Influence of pH on Soil Charge Characteristics and Cadmium Sorption in Some Noncontaminated Soils of Indian Subtropics - Tanmoy Karak; Dilip Kumar Das; Uttam Kumar Singh; Debtanu Maiti (The Scientific World Journal)
Concentrations of total dissolved cadmium (Cd) and activity of its free ions in soil solution are suggested to be influenced by soil pH, organic matter (OM) content, cation exchange capacity (CEC), and clay mineralogy. We investigated the sorption of Cd by taking 25-, 50-, and 100-µM Cd solutions in five noncontaminated soils of West Bengal, India, having differing chemical properties with batch sorption experiments. The charge characteristics and point of zero salt effect (PZSE) of all experimental soils were calculated by the potentiometric titration method measuring the adsorption of H+ and OH– on amphoteric surfaces in solutions of varying ionic strength (I). Sorption of Cd was more pronounced at pH levels greater than PZSE for all experimental soils. The CEC, OM content, clay mineralogy, and specific surface area (SSA) also had a great influence on the sorption of Cd from soil solution to soils. The relationships of Cd with those parameters were found to be consistent and the results concluded that Cd sorption in soils is strongly affected by the soil characteristics.